English as a foreign language lecturers’ language power bases in the high context culture of Toraja - Markus Deli Girik Allo; Nilma Taula’bi’; Elim Trika Sudarsi (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study overviews the English as a foreign language (EFL) lecturers’ language power bases in the high-context culture of Toraja. The writer applied a qualitative study method with a case study design. The writer applied purposive sampling and the subjects of this study are three EFL lecturers. The writer got the data through video observation and interviews. The data analysis technique used is using transcription and coding. It is revealed that the characteristics of lecturers’ behaviors and communication strategies associated with the five bases of power-referent power, coercive power, reward power, legitimate power, and expert power-were observed in the high context culture of Toraja, a common cultural practice among the Toraja learners. Referent power was evident when the lecturer was able to establish a connection with the learners based on shared cultural norms. Coercive power was demonstrated when the lecturer used guilt to pressure learners who were unwilling to do a class presentation. Reward power was characterized by the lecturer providing incentives to learners who complied with requests. Legitimate power was observed when the lecturer maintained strict control over the classroom. Additionally, expert power was identified when the lecturer shared their knowledge and expertise in addressing gaps in the study area.